Hereditary Vitamin D–Resistant Rickets Presenting as Alopecia. Issue 4 (11th June 2014) - Casey, Genevieve; McPherson, Tess; Kini, Usha; Ryan, Fiona; Taibjee, Saleem M.; Moss, Celia; Burge, Susan
Abstract Hereditary vitamin D–resistant rickets (HVDRR) is a rare autosomal recessive disorder caused by mutations in the vitamin D receptor (VDR) gene. We report the case of an infant presenting with alopecia, growth failure, and gross motor developmental delay. Serum biochemistry and skeletal survey were consistent with rickets. After a poor response to standard treatment, genetic testing confirmed a c.147–2A>T novel mutation in the VDR gene consistent with HVDRR. It is important for dermatologists and pediatricians to recognize alopecia as a presenting sign of HVDRR because appropriate treatment leads to better growth and development of the child.